Modeling of Metamaterials in Wave Propagation - Leugering, Günter; Rohan, Eduard; Seifrt, Frantiek (Wave Propagation in Periodic Media, 2010)
This chapter focuses on acoustic, electromagnetic, elastic and piezo-electric wave propagation through heterogenous layers. The motivation is provided by the demand for a better understanding of meta-materials and their possible construction. We stress the analogies between the mathematical treatment of phononic, photonic and elastic meta-materials. Moreover, we treat the cloaking problem in more detail from an analytical and simulation oriented point of view. The novelty in the approach presented here is with the interlinked homogenization- and optimization procedur
EAM Import::2019-03-12

Painting by numbers: Nanoparticle-based colorants in the post-empirical age - Klupp Taylor, Robin; Seifrt, Frantiek; Zhuromskyy, Oleksandr; Peschel, Ulf; Leugering, Günter; Peukert, Wolfgang (Advanced Materials, 2011)
The visual appearance of the artificial world is largely governed by films or composites containing particles with at least one dimension smaller than a micron. Over the past century and a half, the optical properties of such materials have been scrutinized and a broad range of colorant products, based mostly on empirical microstructural improvements, developed. With the advent of advanced synthetic approaches capable of tailoring particle shape, size and composition on the nanoscale, the question of what is the optimum particle for a certain optical property can no longer be answered solely by experimentation. Instead, new and improved computational approaches are required to invert the structure-function relationship. This progress report reviews the development in our understanding of this relationship and indicates recent examples of how theoretical design is taking an ever increasingly important role in the search for enhanced or multifunctional colorants. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhei
Keywords: colloids; core/shell nanoparticles; designed nanostructures; functional coatings; structure-property relationships

Shape optimization for the Helmholtz equation - Seifrt, Frantiek; Leugering, Günter; Rohan, Eduard (Proceedings in Applied Mathematics and Mechanics, 2008)
The aim of our work is to develop optimal dielectric composite structures with specific qualities. The task is to design interfaces of given material components such that the originated structure attains certain optical properties. Propagation of the electromagnetic waves in the composite is described by the Helmholtz equation. Success of the structure is enumerated by the objective function which is to be minimized. Interfaces of the given materials are parametrized by the cubic B–spline curves. The design variables are afterwards the positions of B–spline control points. For objective function evaluation one forward computation of the Helmholtz equation is needed. To get the sensitivity of the objective function we solve the backward (adjoint) equation.